PEMANFAATAN KULIT JERUK SIAM SEBAGAI PESTISIDA ALAMI UTILIZATION OF SIAM ORANGE SKIN AS A NATURAL PESTICIDE - Kiki Kristiandi; Asti Febrina (Jurnal Agrotek Lestari, 2020)
Sambas is one of district lying in West Kalimantan with their agricultural commodities is orange siam. Agricultural products orange siam obtained by Kabupaten Sambas in the year 2016-2018 experienced a significant increase at 24.983.600 kg .This research intended to capitalize on the orange peel siam as a pesticide natural and analyze the type of ingredient in the pesticides. A kind of an orange constituting a variety which has been adopted known and cultivated. West Kalimantan especially Sambas becoming an area of with a monthly granite production of orange siam more or less 9 %. This study was conducted in the Laboratory Agrobisinis Polytechnic State Sambas. The sample purposively technique. The approach that was undertaken is pure experimental. Sample testing was conducted qualitatively and ethanol and given the 10 %, 20 %,30 %, 40 % and 50 % and em4 10 ml, 20 ml, 30 ml, 40 ml and 50 ml research shows that the tannin and the positive sulphur at all treatment given in orange peel he has pesticide natural, the flavonoid positive is in having the treatment, 10 % 20 %, 30 %, 40 % and 50 % and control, not containing positive flavonoid and saponin there are no positive in all the treatment. Alkaloid treatment to found only in control and 50 %.Conclusion in the research are the positive a pesticide natural using orange peel so as to be used natural to pesticides.